Weibull-H-NHE distribution with properties and applications on COVID-19 dataset - Sah Telee, Lal Babu (NCC Journal, 2020)
A new three parameters univariate continuous distribution called Weibull-H-NHE distribution on COVID-19 data with Properties and Applications on COVID-19 data using Weibull-Hclass of distribution is introduced here. Some major properties of model with application on covid-19 data are presented in study. Different curves like probability density, hazard rate, and empirical distribution etc. are included in the study. Parameters are estimated by using method of least square. Model validation is tested by calculating different information criteria values as well as using Q-Q and P-P plots. The applicability of the model is tested on three sets of real data sets. Model application is checked by considering their real data set. All the calculations are done using the R language programming.